The Iron Age Iberian Experimental Pottery Kiln of Verdú, Catalonia, Spain - Ramon Cardona Colell; Josep Pou Vallès; Noelia Calduch Cobos; Borja Gil Limón; José Miguel Gallego Cañamero; Laia Castillo Cerezuela (EXARC Journal, 2014)
The goal of this project is to reconstruct the operational sequence of manufacture of Iberian Iron Age pottery, from clay procurement to firing in a reconstructed kiln. Although pottery is the most characteristic artefact recovered on Iberian Iron Age excavations, most of its complex processes and production techniques remain poorly known. The first phase of this experiment began in 2007 with the construction of a scaled replica of the Iron Age Iberian kiln brought to light at the excavation of Alcalá de Júcar (Province of Albacete). This reconstruction employed materials and techniques identified on the archaeological dig, as well as ethnographic parallels. Some parallels were drawn from the Catalonian town of Verdú, the location of the experiment. This town has an uninterrupted 500 year tradition of ceramic production. The kiln comprised two chambers separated by a grate. Four sensors installed in the kiln recorded a maximum temperature of 600° C. This temperature is probably due to the fact that the kiln was empty during its initial firing. Replicas of Iberian Culture vessels thrown by potters from Verdú were fired in a second experiment. This revealed information regarding the general firing process of vertical updraught kilns in all its complexity, as well as the techniques of temperature control and oxidation and reduction processes, subjects to be examined in future research.